Journal of Latin Linguistics (De Gruyter Mouton, 2013)
The Journal of Latin Linguistics (formerly known as Papers on Grammar) is the only journal devoted entirely to Latin in both synchronic and diachronic perspective. All linguistic phases of Latin - Archaic, Classical, Vulgar, Medieval, Renaissance, Modern - are treated. The journal fills a conspicuous gap in the scientific literature and is arguably the most important journal for Latin linguistics.